ANALISIS KEPUTUSAN PEMBELIAN SMARTPHONE VIVO DI JAKARTA TIMUR (Studi Kasus Pembelian Secara Online Pada Kaum Milenial di E-Commerce) - Farhan Bernardy Haryanto (2021)
This research is a quantitative study that aims to determine the effect of price, promotion, and Design Product on purchase decition. The population in this study were smartphone users who lived or were active in the East Jakarta area. The sample size was taken as many as 75 respondents, with non-probability sampling technique sampling with purposive sampling method. Data collection is done through the spread of google form online questionnaires. The analysis technique used is the inferential & descriptif analysis method through PLS (Partial Least Square) with SmartPLS 3.2 software. The results of this study indicate that (1) Price has a negative and no significant effect onpurchase decitiont with a path coefficient of -0.212, (2) The promotion of a positive and significant influence on purchase decition with a path coefficient of 0,438, (3) Design Product has a positive and significant effect on purchase decition with a path coefficient of 0,634. And has an R- Square value of 0.724.